Pengolahan Limbah Cair Industri Tempe Secara Anaerobik Tipe Fixed-Bed - Aida Soelaeman; Rochmi Widjajanti; Eva Dasmita (Balai Besar Kimia dan Kemasan, 1999)
Tempe, a traditional famous food with a high protein, is usually produced in a small industry. Until now, most of the industries do not treat their wastewater. This research work demonstrates the ability of anaerobic processes type fixed bed process. In fixed bed reactor, grinded anaerobic microorganisms growth on the surface of the media. The result of this research show that, using anaerobic fixed bed process the COD removal rate and gas generated are over 90 % and 70 I/day )for COD inlet about I 0, 000 mg/I).